Urbanization in China The Path to Harmony and Prosperity - Wei, Houkai (Research Series on the Chinese Dream and China's Development Path, 2019)
This book traces the history of urbanization in China and discusses major problems and challenges the country is facing as it undergoes a profound social transformation. The author argues that as China tries to build not just more but also better cities, i.e., cities that are not only economically competitive but also people- and environment-friendly, it should adopt urbanization strategies and policies that promote integrated development for both rural and urban areas, and coordination among otherwise disparate objectives - such as industrialization, ecological modernization, informatization and cultural heritage preservation - nationwide and at various scales.